2012
DOI: 10.1016/j.tiv.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transmission electron microscopy study of titanium dioxide and carbon black nanoparticles uptake in human lung epithelial and fibroblast cell lines

Abstract: Several studies suggest that the biological responses induced by manufactured nanoparticles (MNPs) may be linked to their accumulation within cells. However, MNP internalisation has not yet been sufficiently characterised. Therefore, the aim of this study was to compare the intracellular uptake of three different MNPs: two made of carbon black (CB) and one made of titanium dioxide (TiO(2)), in 16HBE bronchial epithelial cells and MRC5 fibroblasts. Transmission electron microscopy was used to evaluate the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…Finally, the evaluation of the mean diameter of single nanoparticles or agglomerates after an exposure time ranging from 30 min to 2 h suggests that the single nanoparticles aggregated within the cells. Belade et al (2012) observed in MRC5 cells (5 μg/cm 2 of carbon black nanoparticles for 6 h, 24 h and 48 h) a time-dependent increase in the mean diameter of agglomerates. These authors suggested that the cells chiefly incorporated nanoparticles as agglomerates.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, the evaluation of the mean diameter of single nanoparticles or agglomerates after an exposure time ranging from 30 min to 2 h suggests that the single nanoparticles aggregated within the cells. Belade et al (2012) observed in MRC5 cells (5 μg/cm 2 of carbon black nanoparticles for 6 h, 24 h and 48 h) a time-dependent increase in the mean diameter of agglomerates. These authors suggested that the cells chiefly incorporated nanoparticles as agglomerates.…”
Section: Discussionmentioning
confidence: 84%
“…These authors claim that a complete understanding of ZnO nanoparticles fate requires multiple time point observations. To quantify nanoparticles uptake, flow cytometry has mostly been used (Suzuki et al, 2007;Toduka et al, 2012), while the TEM technique is rarely performed (Belade et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nasal mucosa cells Cytotoxic, genotoxic and pro-inflammatory effects [77] Hepatocytes Inflammatory and genotoxic effects [56] Renal cells Cytotoxicity [78] Neurons Neurotoxic effect by disturbing the electrical activity of neuronal networks [7] Lung epithelial cells Cytotoxicity [79] Carbon black nanoparticles (CB-NPs) Lymphocytes Induction of chromosomal aberrations [80] Hepatocytes Hepatotoxicity [81] Neurons Dopaminergic neurons damage pathways [82] Lung epithelial cells Toxicity and inflammatory response. [83] Lymphocytes Cytotoxicity and genotoxicity [84] Silica nanoparticles (SiO 2 ) Fibroblast Cytotoxicity [25] Hepatocytes Genotoxicity, carcinogenicity, hepatotoxicity and inflammation [48,85] Renal cells Induction of oxidative stress and cytotoxicity [86] Neurons Neurotoxicity [7] Lung epithelial cells Genotoxicity, mutagenicity and carcinogenicity [87,88] Lymphocytes Induction of oxidative stress and reduction of immune capacity, Genotoxicity [27,80] Titanium dioxide nanoparticles (TiO 2 )…”
Section: Hepatocytesmentioning
confidence: 99%
“…This is one of the main limitations of spectroscopic methods that moreover are restricted to metallic particles. NPs can be observed inside the cells by transmission electron microscopy, but quantification of their uptake remains time and cost consuming [6]. NP uptake is generally quantified by flow cytometric analysis of fluorescently labeled NPs, [7] or of NPs that have the capacity to scatter the light [8].…”
Section: Introductionmentioning
confidence: 99%